Cambridge handbook of institutional investment and fiduciary duty - Hawley, James P., 1944-; Cambridge eBooks (Cambridge : Cambridge University Press, 2014)
The Cambridge Handbook of Institutional Investment and Fiduciary Duty is a comprehensive reference work exploring recent changes and future trends in the principles that govern institutional investors and fiduciaries. A wide range of contributors offer new perspectives on the dynamics that drive the current emphasis on short-term investment returns. Moreover, they analyze the forces at work in markets around the world which are bringing into sharper focus the systemic effects that investment practices have on the long-term stability of the economy and the interests of beneficiaries in financial, social and environmental sustainability. This volume provides a global and multi-faceted commentary on the evolving standards governing institutional investment, offering guidance for students, researchers and policy-makers interested in finance, governance and other aspects of the contemporary investment world. It also provides investment, business, financial media and legal professionals with the tools they need to better understand and respond to the new financial market challenges of the twenty-first century.
Introduction / James P. Hawley, Andreas G.F. Hoepner, Keith L. Johnson, Joakim Sandberg and Edward J. Waitzer -- Part 1. Fiduciary Duty: A Global Outlook -- Part 2. Fiduciary Duty and the Landscape of Institutional Investment -- Part 3. Challenging Conventional Wisdom on Fiduciary Duty -- Part 4. Towards a Broader Interpretation of Fiduciary Duty -- Part 5. Beneficiaries' Roles and Viewpoints -- Part 6. Fiduciary Duty and Governance.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Institutional investments; Trusts and trustees; Electronic books